FILOSOFI DAN SUMBER HUKUM DALAM BISNIS ISLAM - Muhammad Alif; Muhammad Zidane; Hanif Yasir (Media Riset Bisnis Manajemen Akuntansi, 2025)
This article provides an in-depth overview of the relationship between philosophy and sources of business law in establishing ethical and fair business practices, with an emphasis on Islamic principles. Using a normative approach through library research, the article highlights various elements that form the foundation of business law, including legal theories, regulations, and existing legal practices, while also incorporating Islamic perspectives on justice, fairness, and ethics in business. Additionally, it explains how sources of law such as written law (statutes), customary law, jurisprudence, doctrines, and Islamic legal principles (fiqh) play a crucial role in creating a strong legal framework.Keywords: Business Law, Islamic Law, Islamic Business Ethics, Business and Law, Fiqh (Islamic Jurisprudence)